Determining sensitivity and specificity of the Sport Concussion Assessment Tool 3 (SCAT3) components in university athletes. (19th September 2018) - Downey, Rachel I; Hutchison, Michael G; Comper, Paul
ABSTRACT: Objective : To examine the clinical utility of the Sport Concussion Assessment Tool-3 (SCAT3) in university athletes with concussion in the absence and presence of baseline data over time. Methods : Athletes with concussion ( n = 23) and uninjured controls ( n = 22) were prospectively evaluated at three time-points (baseline, 3–5 days, 3 weeks post-injury) with the SCAT3 components: (1) Post-Concussion Symptom Scale (PCSS); (2) Standardized Assessment of Concussion (SAC); and (3) modified Balance Error Scoring System (m-BESS). Sensitivity and specificity were calculated using reliable change indices and normative data from 458 athletes who completed baseline testing. Results : The PCSS total symptom score yielded highest sensitivity (47.4–72.2%) and specificity (78.6–91.7%) 3–5 days post-injury, with the SAC and m-BESS demonstrating little discriminative ability when used more than 3 days post-concussion. The utility of the SCAT3 was comparable when baseline or normative data was used for predicting concussion. Conclusion : The SCAT is a clinically useful tool for assessing concussion in the absence or presence of baseline data within the first 3–5 days post-injury. Clinical utility of the SCAT3 was driven by symptoms, which remains consistent in the SCAT5. Future research should explore whether additional cognitive elements in the SCAT5 improve utility beyond this timeframe.